Clinical value of fibroblast growth factor 19 in predicting gastrointestinal dysfunction in patients with sepsis - Guan, Linsai; Wang, Feiyao; Chen, Jingni; Xu, Yanxin; Zhang, Weixing; Zhu, Jianping (Frontiers in Nutrition, 2024)
Objective To assess the potential value of fibroblast growth factor 19 (FGF19) as a predictor of gastrointestinal (GI) dysfunction in patients with sepsis. Methods A prospective study was conducted, and 209 patients who were diagnosed with sepsis and admitted to the intensive care unit (ICU) at teaching hospitals in China were enrolled from June 2023 to December 2023. The serum FGF19 level was determined at ICU admission. The differences in serum FGF19 levels between the two groups were compared via the Mann‒Whitney U test, and Spearman’s correlation coefficient was used to identify the correlations of the FGF19 concentration with other clinical variables and biomarkers. Receiver operating characteristic (ROC) analysis was used to determine the value of FGF19 in predicting GI dysfunction in patients with sepsis. Results The total ICU mortality rate was 13.3% (24/180). There was a tendency toward increased ICU mortality in patients with sepsis-associated GI dysfunction compared with patients without GI dysfunction with statistical significance (21.9% vs 8.6%, P=0.031). Serum FGF19 levels were significantly higher in patients with sepsis-associated GI dysfunction than in patients without GI dysfunction [355.1(37.2,2315.4)μg/mL vs 127.4(5.7,944.2)μg/mL,P=0.003]. The results of receiver operating characteristic (ROC) curve analysis revealed that the area under the ROC curve (AUC) for the ability of FGF19 to predict GI dysfunction in patients with sepsis was 0.773(95% CI 0.712~0.827), which was greater than the predictive capacity of PCT [AUC=0.632 (95% CI 0.562~0.804)]. Conclusion Serum FGF19 could be considered as a novel predictor or biomarker of GI dysfunction in patients with sepsis.